1989
DOI: 10.1002/bip.360280118
|View full text |Cite
|
Sign up to set email alerts
|

Cyclo(D‐Pro‐L‐Pro‐D‐Pro‐L‐Pro): Structural properties and cis/trans isomerization of the cyclotetrapeptide backbone

Abstract: Ulm, Federal Republic of Gennany SynopsisCombinations of L-and D-proline residues are useful compounds for finding new structures and properties of cyclic peptides. This is demonstrated with one striking example, the cyclic tetrapep-For this molecule composed of strictly alternating D-and L-configurated residues, a highly symmetrical structure is expected, which should be an optically inactive meso-form. Cyclization of the enantiomeric pure linear precursor D-P~o-L-P~o-D-P~o-L-P~o, however, yields a racemic mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…22,44 at the University of Ulm to examine the influence of substituting D-amino acid residues on the backbone conformation of an Lamino acid peptide by performing cyclization reactions on diastereomeric D,L-oligoprolines. These are the source of the complete series of N-terminally Boc-protected ( Boc=tert-butyloxycarbonyl) peptide sequences with 3 to 8 alternate D-and L-proline residues used in this study, which include Boc-LDL-Pro3, BOC-DLDL-PTO~, and BOC-DLDLDLDL-Pr08, using the notation introduced above.…”
Section: Experimental Peptide Materialsmentioning
confidence: 99%
“…22,44 at the University of Ulm to examine the influence of substituting D-amino acid residues on the backbone conformation of an Lamino acid peptide by performing cyclization reactions on diastereomeric D,L-oligoprolines. These are the source of the complete series of N-terminally Boc-protected ( Boc=tert-butyloxycarbonyl) peptide sequences with 3 to 8 alternate D-and L-proline residues used in this study, which include Boc-LDL-Pro3, BOC-DLDL-PTO~, and BOC-DLDLDLDL-Pr08, using the notation introduced above.…”
Section: Experimental Peptide Materialsmentioning
confidence: 99%
“…54,55 Also, Mästle et al 56 reported that the two different enantiomers isolated from the racemic mixture of a cyclic tetrapeptide, cyclo͑D-Pro-L-Pro-D-Pro-L-Pro͒ show, qualitatively, almost completely inverse CD spectra, in which the enatiometric compound B has the negative n* bands around 230 nm. This may be explained by the fact that these two cycloenantiomers have symmetrically opposite ring directions ͑opposite helical senses͒.…”
Section: B An Amide Parameterization Of Small Cyclic Peptides Involvmentioning
confidence: 99%
“…Unlike cyclic tripeptides and pentapeptides which contain either only cis-, or largely transamide bonds, respectively, CTPs contain a mixture of both cis-and trans-peptide bonds. 24 This ''sweet spot'' of CTPs seems ideal for fine tuning of various rigid structures since the positions of cis/trans-amide bonds largely determines the conformation of the mimetic scaffold. The CTP c[Pro-proPro-pro] is a combination of these two reverse-turn mimetic approaches shown to exist with stable cis-trans-cis-trans and trans-cis-trans-cis amide bond conformers at room temperature in water.…”
Section: Introductionmentioning
confidence: 99%